The Effects of Budget Deficits on Selected Macroeconomic Variables in Nigeria and Ghana (1970 – 2013) - Nelson, Nkalu Chigozie (Asian Journal of Empirical Research, 2015)
This study investigates the effects of budget deficits on selected macroeconomic variables in Nigeria and Ghana using annual time-series data of both economies covering from 1970 to 2013; and taking previous empirical studies as its point of departure. The specific objectives of the study include: to examine the effects of budget deficits on interest rates, inflation, and economic growth in Nigeria and Ghana within the methodological framework of Seemingly Unrelated Regression (SUR) model and Two-Stage Least Squares (2SLS). The study employs Eagle-Granger Cointegration test, Augmented Dickey Fuller (ADF) and Phillips-Perron (PP) tests in estimating the systems equations. Data sourced from World Bank, IMF - World Economic Outlook, Central Bank of Nigeria, Bank of Ghana and others, were analyzed using SUR model with several diagnostic and specification tests to examine the objectives of the study. From the perspective of this study, the empirical findings demonstrated that budget deficit has statistically negative effects on interest rate, inflation, and economic growth thereby supporting the neoclassical argument in the literature that budget deficit slows growth of the economy through resources crowding-out. Based on the empirical findings, appropriate recommendations were made for both Nigeria and Ghana economies.